2018
DOI: 10.1021/acs.inorgchem.8b00902
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Lone-Pair–Surface Bonds and Their Scaling Relations

Abstract: We investigate the (surface) bonding of a class of industrially and biologically important molecules in which the chemically active orbital is a 2 p electron lone pair located on an N or O atom bound via single bonds to H or alkyl groups. This class includes water, ammonia, alcohols, ethers, and amines. Using extensive density functional theory (DFT) calculations, we discover scaling relations (correlations) among molecular binding energies of different members of this class: the bonding energetics of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 200 publications
4
43
0
Order By: Relevance
“…Thus, as a large amount of the ethanol adsorption energy arises from dispersion interactions, which are not largely affected by the Pt nanoparticle size, and as we see a small interaction between ethanol and d states from the Pt surface, it is understandable that nanoparticle size effects are less important for ethanol adsorption. Additionally, a recent work from Kakekhani et al 90 demonstrated that the covalent contributions can be much less important for the adsorption energies of closedshell adsorbates such as water, alcohols, ammonia, on metallic surfaces than for unsaturated intermediates such as O, OH, CO. The authors show that the correlation slope between adsorption energies of water and O is small, helping to explain the small slope in the correlation between ethanol adsorption energies and descriptors such as the generalized coordination number or d-band centres, which can successfully describe the O adsorption.…”
Section: Structural and Electronic Changes For Adsorbates Interactingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, as a large amount of the ethanol adsorption energy arises from dispersion interactions, which are not largely affected by the Pt nanoparticle size, and as we see a small interaction between ethanol and d states from the Pt surface, it is understandable that nanoparticle size effects are less important for ethanol adsorption. Additionally, a recent work from Kakekhani et al 90 demonstrated that the covalent contributions can be much less important for the adsorption energies of closedshell adsorbates such as water, alcohols, ammonia, on metallic surfaces than for unsaturated intermediates such as O, OH, CO. The authors show that the correlation slope between adsorption energies of water and O is small, helping to explain the small slope in the correlation between ethanol adsorption energies and descriptors such as the generalized coordination number or d-band centres, which can successfully describe the O adsorption.…”
Section: Structural and Electronic Changes For Adsorbates Interactingmentioning
confidence: 99%
“…40 The bond lengths contractions and d-band centre downshifts are associated with weaker adsorption energies and can be used to explain the support effect for O and CO. For ethanol, our previous results demonstrated that the Pt-Pt bond lengths and d-band centre changes induced by size effects are not able to change the ethanol adsorption energies to this extent. Recently, Seminovski et al 91,92 and Kakekhani et al 90 demonstrated that the ethanol adsorption is stronger on cationic adsorption sites and that in some cases the electrostatic effects can be dominant. 90 Thus, a possible explanation for the support effect for ethanol adsorption can be the change in the atomic charges for the surface Pt atoms.…”
Section: O Co and Ethanol Interacting With Pt Nanoparticles Supportmentioning
confidence: 99%
“…32,[42][43][44] Recent theoretical work has provided a systematic understanding of of how various surface properties affect surface binding of water. 45 Several studies have also investigated the effects of explicitly including pH. 40,46,47 Although the reaction thermochemistry is often investigated without the explicit consideration of the electrolyte, 48 it has been demonstrated that ions can significantly affect the thermodynamics due to field effects.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from atomic adsorbates and their hydrogenated homologues at the interface,b ifunctionally bound species,a dsorbing on both Au and MgO components,a lso exhibit linear scaling.F or example, COOH* ( (Table 1; Supporting Information, Figure S10), CH 3 OH*( Supporting Information, Figure S11), and CH 3 CH 2 OH* (Supporting Information, Figure S12), which have been shown to exhibit scaling properties owing to lone-pair interactions on metals, [29] also display scaling trends at the Au/MgO interface.F urther examples of SRs involving WGS and methanol synthesis intermediates are provided in Table S4 of the Supporting Information. Overall, the SRs show minimal scatter,w ith aMAE of 0.05 eV across SRs for 31 adsorbates.…”
mentioning
confidence: 99%